The structural and optical properties of neodymium doped lithium niobate and yttrium aluminum garnet single crystals [electronic resource] - Nurul Wahidah Zainal Abidin Sham, 1989-, author 497468; Fakulti Sains 8004 (2015)
Thesis (Sarjana Sains (Fizik))